Docking‐based three‐dimensional quantitative structure–activity relationship (3D‐QSAR) predicts binding affinities to aryl hydrocarbon receptor for polychlorinated dibenzodioxins, dibenzofurans, and biphenyls. (28th May 2013) - Yuan, Jintao; Pu, Yuepu; Yin, Lihong
Abstract Polychlorinated dibenzodioxins (PCDDs), polychlorinated dibenzofurans (PCDFs), and polychlorinated biphenyls (PCBs) cause toxic effects after binding to an intracellular cytosolic receptor called the aryl hydrocarbon receptor (AhR). Thymic atrophy, weight loss, immunotoxicity, acute lethality, and induction of cytochrome P4501A1 have all been correlated with the binding affinity to AhR. To study the key molecular features for determining binding affinity to AhR, a homology model of AhR ligand‐binding domains was developed, a molecular docking approach was employed to obtain docking‐based conformations of all molecules in the whole set, and 3‐dimensional quantitative structure–activity relationship (3D‐QSAR) methodology, namely, comparative molecular field analysis (CoMFA), was applied. A partial least square analysis was performed, and QSAR models were generated for a training set of 59 compounds. The generated QSAR model showed good internal and external statistical reliability, and in a comparison with other reported CoMFA models using different alignment methods, the docking‐based CoMFA model showed some advantages. Environ Toxicol Chem 2013;32:1453–1458. © 2013 SETAC